Lionfish abundance, size structure and spatial distribution along the Venezuelan coast (Pterois volitans, Pteroinae: Scorpaenidae) Esteban A. Agudo1 & Eduardo Klein Salas2 - Agudo, Esteban A. (2014)
The recent invasion of lionfish (Pterois volitans) in the Atlantic is considered a new threat to benthic and fish communities in the Caribbean region. This species was first reported in Venezuela in 2009 at various sites. Increasing reports in the past five years suggest lionfish has expanded its range of distribution and habitats. Nevertheless, this information is mostly anecdotal and extensive surveys aimed to determine its abundance, size structure and other ecological aspects encompassing wider spatial scales are necessary to understand the actual role of this species on sub-tidal marine communities in Venezuela. We determined its density and population size structure through visual census along the Venezuelan coast. Visual censuses were made following strip transects at a depth between 5 and 20m and in daylight time, at 19 sites in five localities. Average density ranged between 7 to 55 individuals per hectare among sites. Most individuals were adults and most were found in caves, coexisting with other lionfish or with different species, while others were actively preying. The fish Pterois volitans seems to be well-established along the Venezuelan coast in densities that in some sites appear to be higher than in their Pacific native range but lower than in some invaded localities of the Atlantic. Rev. Biol. Trop. 62 (Suppl. 3): 151-158. Epub 2014 September 01.